An Analysis of The Bio-Battery Efficiency from Fruits and Vegetables’ Waste as An Alternative to Energy Sources - Sasongko, Adam Arya; Bachri, Affan; Laksono, Arief Budi (Evolution of Information, Communication and Computing System, 2025)
Global warming and increasing air pollution have encouraged humans to continue to develop various environmentally friendly energies. One solution that can be taken is the development of bio-batteries, an energy storage system using microorganisms as an energy source. Bio-batteries promise environmentally friendly energy because they utilize organic waste. In this research, a bio-battery will be designed using electrolyte paste from several fruit and vegetable wastes, including oranges, mangoes, bananas, papaya, tomatoes and star fruit. These fruits and vegetables have previously been mashed and added with electrolyte liquid and then put into used batteries which have been cleaned from the manganese oxide which is the content of the battery. Then a comparison was also carried out with conventional batteries to determine the level of efficiency of these fruit and vegetable waste bio-batteries. This research shows that fruit and vegetable waste is less efficient if used as a substitute for manganese oxide or electrolyte in unused batteries. Because when compared to conventional batteries, the highest efficiency value for bio-batteries only reaches 32.47% for tomato waste bio-batteries and the lowest efficiency value is 4.77% for banana waste bio-batteries.